Quantifying Human Subjectivity Using Q Method: When Quality Meets Quantity - Kamal, Sristi; Kocór, Marcin; Grodzińska-Jurczak, Małgorzata (Qualitative Sociology Review, 2014)
Incorporating human subjectivity in applied disciplines of social sciences and other base sciences poses a challenge as the nature of qualitative data is often the point of contention. Q methodology is a tool that addresses this challenge as it helps quantify qualitative data using Q factor analysis. Initially developed for psychology and political sciences, Q methodology now finds its use in many research disciplines of science, especially in interdisciplinary studies that take into account human subjectivity. This article provides a detailed description on the various steps involved in conducting a Q study, with special emphasis on data interpretation. To describe the methodology and demonstrate data interpretation, we used data from our pilot case study of socio-ecological nature that documents attitudes of people towards nature conservation on private land. Additionally, we mention the specific usefulness of this method, highlight the potential challenges at each step of the approach, and provide practical advice to overcome them. In our opinion, Q methodology has been more restricted in its use on the ground of being a more social or psychological tool, and therefore, our aim is to familiarize researchers who could be interested in a mixed approach of joining quantitative data analysis with qualitative, in-depth interpretation with the approach at hand.